Optical Properties of Hybrid Organic-Inorganic Materials and their Applications - Parola, Stephane; Julián-López, Beatriz; Carlos, Luís D.; Sanchez, Clément (Advanced functional materials, 2016)
Research on hybrid inorganic‐organic materials has experienced an explosive growth since the 1980s, with the expansion of soft inorganic chemistry based processes. Indeed, mild synthetic conditions, low processing temperatures provided by “chimie douce” and the versatility of the colloidal state allow for the mixing of the organic and inorganic components at the nanometer scale in virtually any ratio to produce the so called hybrid materials. Today a high degree of control over both composition and nanostructure of these hybrids can be achieved allowing tunable structure‐property relationships. This, in turn, makes it possible to tailor and fine‐tune many properties (mechanical, optical, electronic, thermal, chemical…) in very broad ranges, and to design specific multifunctional systems for applications. In particular, the field of “Hybrid‐Optics” has been very productive not only scientifically but also in terms of applications. Indeed, numerous optical devices based on hybrids are already in, or very close, to the market. This review describes most of the recent advances performed in this field. Emphasis will be given to luminescent, photochromic, NLO and plasmonic properties. As an outlook we show that the controlled coupling between plasmonics and luminescence is opening a land of opportunities in the field of “Hybrid‐Optics”. This review reports the latest works on hybrid optical materials. It gives an insight in the state‐of‐the‐art in the field of hybrid materials devoted to optics and in particular the relationship between the different types of structure, the organic‐inorganic interfaces and the final properties of the systems.